2017
DOI: 10.1016/j.bpj.2016.11.151
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of a Calcium-Activated Cation Channel From Tsukamurella Paurometabola

Abstract: The selectivity filter is an essential functional element of K þ channels that is highly conserved both in terms of its primary sequence and its three-dimensional structure. Here, we investigate the properties of an ion channel from the Gram-positive bacterium Tsukamurella paurometabola with a selectivity filter formed by an uncommon proline-rich sequence. Electrophysiological recordings show that it is a non-selective cation channel and that its activity depends on Ca 2 þ concentration. In the crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The strength of the electric field E , specified in units V/nm, was chosen such that the product E · L with the box dimension in axial direction ( L = 14.626 nm) resulted in voltages of −0.2, 0.0, 0.2, 0.3 and 0.5 V 64 . Although high in physiological terms, voltages of this strength are commonly used in MD simulations and have proven to yield good results in the past 65 67 . Of each run, lasting 100 ns, the first 10 ns were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The strength of the electric field E , specified in units V/nm, was chosen such that the product E · L with the box dimension in axial direction ( L = 14.626 nm) resulted in voltages of −0.2, 0.0, 0.2, 0.3 and 0.5 V 64 . Although high in physiological terms, voltages of this strength are commonly used in MD simulations and have proven to yield good results in the past 65 67 . Of each run, lasting 100 ns, the first 10 ns were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the complications associated with parameterization of polarizable force fields, and higher computational overhead for MD runs, hybrid polarizable/additive and fully polarizable models have been used for prototypical gramicidin A ion channel simulations Patel et al 2009;Vorobyov et al 2010;Peng et al 2016), demonstrating reduced free energy barriers and thus providing more accurate channel conductance. And, fully polarizable MD simulations were reported recently for other ion channels as well (Dhakshnamoorthy et al 2016;Kratochvil et al 2016;Sun & Gong, 2017).…”
Section: Figure 2 a Typical Ion Channel All-atom MD Simulation Systementioning
confidence: 98%
“…And, fully polarizable MD simulations were reported recently for other ion channels as well (Dhakshnamoorthy et al . ; Kratochvil et al . ; Sun & Gong, ).…”
Section: Introductionmentioning
confidence: 99%
“…The structural, functional and computational data provide a characterization of this calcium-gated cationic channel. (17) Nucleic Acids Studies have shown the importance of polarization for capturing the flexibility and stacking behavior of nucleic acids with ions. (34,106,146) Gresh et.…”
Section: Diffusion and Permeation Of Small Moleculesmentioning
confidence: 99%